PENGARUH VIDEO MEDIA DONGENG TERHADAP PENGEMBANGAN KEMAMPUAN MENYIMAK ANAK KELOMPOK B DI TAMAN KANAK-KANAK MENTARI KABUPATEN TAKALAR - Nur Aziza; Herlina Herlina; A Sri Wahyuni Asti (incrementapedia, 2021)
The problem of this research is the low level of listening to children in fairy tale activities. the formulation of the problem is whether there is an effect of fairy tale media video activities on the developmentn of children’s listening skills. This study aims to determine the effect of fairy tale video media activities on the development of children’s listening skills. The hypothesis of this research is that if fairy tale media videos are applied in learning, children’s listening can increase. This research approach is quantitative with the type of research is quasi experimental design consisting of two groups, namely the experimental and control groups, with a research design that is non equivalent control group design. The variables of this study were fairy tales media video (independent variable) and listening to children (dependent variable). This study took place at mentari kindergarten, takalar regency with the subject of research on the influence of fairy tale video media consisting of 14 children, namely 7 children (control group) and 7 children (experimental group). Test data documentation with quantitative analysis. The conclusion of this study is that children’s listening increases.